2017
DOI: 10.1093/mnras/stx1440
|View full text |Cite
|
Sign up to set email alerts
|

A Universe of ultradiffuse galaxies: theoretical predictions from ΛCDM simulations

Abstract: A particular population of galaxies have drawn much interest recently, which are as faint as typical dwarf galaxies but have the sizes as large as L * galaxies, the so called ultra-diffuse galaxies (UDGs). The lack of tidal features of UDGs in dense environments suggests that their host halos are perhaps as massive as that of the Milky Way. On the other hand, galaxy formation efficiency should be much higher in the halos of such masses. Here we use the model galaxy catalog generated by populating two large sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
138
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(169 citation statements)
references
References 66 publications
28
138
2
1
Order By: Relevance
“…This would mean that they also exist in lower-density environments, albeit with possibly more disk-like morphologies. Rong et al (2017) reached a similar conclusion based on semianalytic galaxy formation models. Di Cintio et al (2017) used the NIHAO simulation to study the formation of UDG-type galaxies, and they also suggested that internal processes, particularly outflow-driven feedback, may be responsible for their formation.…”
Section: Introductionsupporting
confidence: 66%
“…This would mean that they also exist in lower-density environments, albeit with possibly more disk-like morphologies. Rong et al (2017) reached a similar conclusion based on semianalytic galaxy formation models. Di Cintio et al (2017) used the NIHAO simulation to study the formation of UDG-type galaxies, and they also suggested that internal processes, particularly outflow-driven feedback, may be responsible for their formation.…”
Section: Introductionsupporting
confidence: 66%
“…Right: Normalised comparison with observations of HI-bearing field UDGs in the literature (Leisman et al 2017). and predictions from the semi-analytical models (SAM) of Rong et al (2017) and Jones et al (2018). Poisson error-bars are shown.…”
Section: Comparison With Hi-bearing Udgsmentioning
confidence: 99%
“…One particularity relevant piece of work is that of Leisman et al (2017) and Jones et al (2018), who have shown that not only do HI-bearing UDGs exist in the field (as theoretically predicted by Di Cintio et al 2017), but also that their number density is too high to be explained by an extrapolation of the empirical relation between the number of UDGs and M halo measured by van der Burg et al (2017). Further, their sample appear systematically bluer than anticipated for UDGs in the field when compared with semi-analytic models (Rong et al 2017;Jones et al 2018). However, this analysis was limited to HI-rich field UDGs and it is unknown how this population relates to the overall field UDG population.…”
Section: Introductionmentioning
confidence: 97%
“…Yozin & Bekki 2015;Zaritsky 2017;Sifón et al 2018;Amorisco et al 2018) and theoretical ones (e.g. Amorisco & Loeb 2016;Di Cintio et al 2017;Rong et al 2017;Chan et al 2018;Liao et al 2019;Jiang et al 2019) found that UDGs span a wide range of physical properties, and perhaps a correspondingly large range of origin stories.…”
Section: Introductionmentioning
confidence: 99%